Protection changes the relevancy of scales of variability in coralligenous assemblages. (20th June 2016) - Piazzi, L.; La Manna, G.; Cecchi, E.; Serena, F.; Ceccherelli, G.
Abstract: The knowledge of natural spatial patterns of variability is crucial to discriminate between natural changes and human-induced effects and to plan monitoring programs and impact evaluation studies. The present study aimed at estimating the spatial variability of coralligenous habitat, one of the main important habitats of the Mediterranean Sea, at several spatial scales. Specifically, the following hypotheses were tested: i) the structure of coralligenous assemblage and ii) the abundance of main taxa/groups both changed among different spatial scales differently depending on protection. A hierarchical sampling design was used to study 14 localities (7 Marine Protected Areas and 7 unprotected) at multiple spatial scales through photographic recording. The study suggested that, in protected conditions, the structure of coralligenous assemblages mostly varied at small spatial scale (m apart), while the structure is similar across different localities, sites and areas, even if the abundance of the main taxa/morphological groups changed. In unprotected conditions, variability among localities was higher than among Marine Protected Areas, while an opposite trend was observed at the smaller spatial scales. Highlights: The study aimed at estimating the spatial variability of coralligenous habitat. Seven MPAs and seven unprotected localities were studied at multiple spatial scales. In MPAs coralligenous assemblages mostly varied at small spatial scale. In unprotected conditions, variability among localities was higher than among MPAs. Spatial heterogeneity was higher in all MPAs compared to unprotected localities.